A new species of Tereancistrum (Monogenea, Dactylogyridae) from the gills of three Leporinus species (Characiformes, Anostomidae) and a revised description of Tereancistrum parvus - Zago, Aline C. [UNESP]; Yamada, Fábio H. [UNESP]; Franceschini, Lidiane [UNESP]; Bongiovani, Marcela F. [UNESP]; Yamada, Priscilla O. F. [UNESP]; da Silva, Reinaldo J. [UNESP] (FapUNIFESP (SciELO), 2017)
The present study describes Tereancistrum flabellum n. sp. (Dactylogyridae, Ancyrocephalinae) from the gills of the anostomid fishes Leporinus friderici, Leporinus amblyrhynchus and Leporinus elongatus from two freshwater ecosystems in the south east of Brazil. This new species is mainly characterized by the morphology of the copulatory complex (such as the MCO base formed by two fan-shaped structures, and accessory piece flattened, curved, rigid and channeled), a dorsal anchor with a well-developed superficial and inconspicuous deep root, and the shape of the accessory anchor sclerite with small spathulate termination. Tereancistrum flabellum n. sp. is the first record of a dactylogyrid from L. amblyrhynchus. The description of Tereancistrum parvus is also emended to correct and complement previous descriptions and the species is reported for the first time in Schizodon nasutus.
Keywords: Ancyrocephalinae; Anostomid fish; Gill ectoparasites; Monogeneans; Neotropical region